2021
DOI: 10.3390/ijms22179363
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Alpha-Actinin Proteins in Platelet Formation and Function, and Their Causative Role in Congenital Macrothrombocytopenia

Abstract: The actin cytoskeleton plays a central role in platelet formation and function. Alpha-actinins (actinins) are actin filament crosslinking proteins that are prominently expressed in platelets and have been studied in relation to their role in platelet activation since the 1970s. However, within the past decade, several groups have described mutations in ACTN1/actinin-1 that cause congenital macrothrombocytopenia (CMTP)—accounting for approximately 5% of all cases of this condition. These findings are suggestive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 93 publications
(177 reference statements)
0
11
0
Order By: Relevance
“…Importantly, RhoA GTPases are master orchestrators of platelet physiology by inducing the vascular effects of various vasoactive factors to promote hemostasis, and play a major role in the development of cardiovascular disease [ 50 , 51 ]. ROCK1/2 inhibition increased megakaryocytes ploidy, aberrant proplatelet release, and macrothrombocytopenia [ 52 54 ]. Interestingly, another study found that both macrothrombocytopenia and an increase in LV fractional shortening were associated with a more hypercoagulable hemostatic system in dogs with MMVD.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, RhoA GTPases are master orchestrators of platelet physiology by inducing the vascular effects of various vasoactive factors to promote hemostasis, and play a major role in the development of cardiovascular disease [ 50 , 51 ]. ROCK1/2 inhibition increased megakaryocytes ploidy, aberrant proplatelet release, and macrothrombocytopenia [ 52 54 ]. Interestingly, another study found that both macrothrombocytopenia and an increase in LV fractional shortening were associated with a more hypercoagulable hemostatic system in dogs with MMVD.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, as a scaffolding protein, α-actinin coordinates the organization of various actin-based structures, from sarcomeres to focal adhesions [ 84 ]. Mutations in α-actinin isoforms are linked to several human diseases, such as autosomal-dominant congenital macrothrombocytopenia [ 85 , 86 ], dilated or hypertrophic cardiomyopathy [ 87 ], familial focal segmental glomerulosclerosis (FFSG) [ 88 , 89 ], carcinomas [ 90 , 91 ], and immunological diseases [ 92 ].…”
Section: Actin-bundling Proteinsmentioning
confidence: 99%
“…Mutations in α-actinin-1 lead to focal segmental glomerulosclerosis [ 89 ] and congenital macrothrombocytopenia [ 97 , 98 ]. This correlates with the knock-down of this protein, preventing megakaryocyte polyploidization that is essential for platelet production [ 86 ]. Mutations in ACTN4, encoding α-actinin-4 that binds actin more strongly than the wild-type (WT) protein, cause familial focal segmental glomerulosclerosis [ 88 , 99 ].…”
Section: Actin-bundling Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding regions of the α-actin molecule dimerize into rod-like structures that allow for cross-linking of actin filaments into bundles. In cooperation with other cytoskeletal proteins, actin filaments play an important role in platelet morphology [3]. A disruption of actin filament cross-linking appears to disrupt cytoplasmic organization, according to electron microscopy and immunofluorescence studies of affected megakaryocytes [4].…”
Section: Introductionmentioning
confidence: 99%